2001
DOI: 10.1074/jbc.m004812200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glycogen Synthesis by Amino Acids in Cultured Human Muscle Cells

Abstract: Insulin and a number of metabolic factors stimulate glycogen synthesis and the enzyme glycogen synthase. Using human muscle cells we find that glycogen synthesis is stimulated by treatment of the cells with lithium ions, which inhibit glycogen synthase kinase 3. Insulin further stimulates glycogen synthesis in the presence of lithium ions, an effect abolished by wortmannin and rapamycin. We report also that amino acids stimulate glycogen synthesis and glycogen synthase, these effects also being blocked by rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 44 publications
2
75
1
Order By: Relevance
“…Hence, we examined the effect of combined inhibition of GSK-3b and p70S6K, and induction of DNAdamage. We used lithium chloride to inhibit GSK-3b, nonessential amino-acid (NEAA) restriction to inhibit p70S6K 16 and cisplatin, a key chemotherapeutic drug for bladder cancer and a known inducer of DNA-damage and p70S6K cleavage, to induce DNA-damage. 17 Blebbishield-mediated sphere formation after apoptosis and its dependence on amino acid-p70S6K signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we examined the effect of combined inhibition of GSK-3b and p70S6K, and induction of DNAdamage. We used lithium chloride to inhibit GSK-3b, nonessential amino-acid (NEAA) restriction to inhibit p70S6K 16 and cisplatin, a key chemotherapeutic drug for bladder cancer and a known inducer of DNA-damage and p70S6K cleavage, to induce DNA-damage. 17 Blebbishield-mediated sphere formation after apoptosis and its dependence on amino acid-p70S6K signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous other stimuli also lead to inactivation of GSK-3 through S9/S21 phosphorylation, including growth factors such as EGF and PDGF that stimulate the GSK-3-inactivating kinase p90 RSK (also known as MAPKAP-K1) through MAP kinases (Brady et al, 1998;Saito et al, 1994), activators of p70 ribosomal S6 kinase (p70S6K) such as amino acids, (Armstrong et al, 2001;Krause et al, 2002;Terruzzi et al, 2002), activators of cAMP-activated protein kinase (PKA) (Fang et al, 2000;Li et al, 2000;Tanji et al, 2002) and PKC activators (Ballou et al, 2001;Fang et al, 2002).…”
Section: Gsk-3 Phosphorylation: Insights From Crystal Structures 1) Tmentioning
confidence: 99%
“…The inhibition of GSK3 could alter the balance between this enzyme and PP-1, leading to dephosphorylation of glycogen synthase and its subsequent activation. But, together with an implication of PKB in the stimulation of glucose uptake and glycogen synthesis by insulin (Ueki et al 1998), it has been shown that direct inhibition of GSK3 in liver cells increases glycogenesis (Armstrong et al 2001); thus, a combined mechanism of both might exist. In addition, some authors have provided evidence for a contribution of a rapamycin-sensitive signalling pathway, involving p70s6k, to the control of glycogen synthesis (Shepherd et al 1995, Hurel et al 1996.…”
Section: Introductionmentioning
confidence: 99%